Distinct time trends in colorectal cancer incidence in countries with SDI levels from 1990 to 2019: an age–period–cohort analysis for the Global Burden of Disease 2019 study - Zhang, Yan; Zhang, Xun-Bing; Ding, Yu-Wei; Kong, Yang; Zhu, Xiao-Feng; Li, Pu-Heng; Tian, Yang; Zhang, Qing-Wei (Frontiers in Public Health, 2024)
In 2019, the incidence of CRC was 2.17 (95% UI 2.00–2.34) million, of which China, the United States of America, and Japan had the highest incidence population, accounting for 45.9% of the global population. The age–standardized incidence rate (ASIR) was 26.7 (95% UI 28.9–24.6) per 100,000 people, of which 30 countries had an incidence rate greater than 40.0 per 100,000 people. From 1990 to 2019, the middle SDI region had the largest increase in incidence rate, with a net drift of 2.33% (95% CI 2.2%–2.46%, P< 0.001). Globally, the incidence population was concentrated in the age group of 50–69 years, and the age group of 30–34 years had the largest increase in incidence rate (local drift 1.19% (95% CI 1.01%–1.37%)). At the same time, the sex and age distributions of CRC incidence had significant heterogeneity across regions and countries. In the past 30 years, the incidence rate in 31 countries has been well controlled (net drift <0), and most of them were concentrated in high–and high–middle–SDI regions, such as Australia, Czechia, and Belgium, and the relative risk of incidence generally improved over time and consecutive young birth cohorts. CRC incidence showed an unfavorable trend (net drift ≥1%) in 89 countries, of which 27 countries were more significant (net drift >2%), mostly concentrated in the middle SDI region, such as China, Mexico, and Brazil, and the risk of period and birth cohort was unfavorable.